Adenosine Receptors in Modulation of Central Nervous System Disorders - Choudhury, Hira; Chellappan, Dinesh K.; Sengupta, Pallav; Pandey, Manisha; Gorain, Bapi (Current Pharmaceutical Design, 2019)
The ubiquitous signaling nucleoside molecule, adenosine is found in different cells of the human body to provide its numerous pharmacological role. The associated actions of endogenous adenosine are largely dependent on conformational change of the widely expressed heterodimeric G-protein-coupled A1, A2A, A2B, and A3 adenosine receptors (ARs). These receptors are well conserved on the surface of specific cells, where potent neuromodulatory properties of this bioactive molecule reflected by its easy passage through the rigid blood-brainbarrier, to simultaneously act on the central nervous system (CNS). The minimal concentration of adenosine in body fluids (30–300 nM) is adequate to exert its neuromodulatory action in the CNS, whereas the modulatory effect of adenosine on ARs is the consequence of several neurodegenerative diseases. Modulatory action concerning the activation of such receptors in the CNS could be facilitated towards neuroprotective action against such CNS disorders. Our aim herein is to discuss briefly pathophysiological roles of adenosine on ARs in the modulation of different CNS disorders, which could be focused towards the identification of potential drug targets in recovering accompanying CNS disorders. Researches with active components with AR modulatory action have been extended and already reached to the bedside of the patients through clinical research in the improvement of CNS disorders. Therefore, this review consist of recent findings in literatures concerning the impact of ARs on diverse CNS disease pathways with the possible relevance to neurodegeneration.
Keywords: adenosine receptors